LAST REFLECTIONS ON A WAR : Bernard B. Fall's last comments on Vietnam - Fall, Bernard B., 1926-1967 (Stackpole Books, 2000)
Last Reflections on a War stands as a fine representative sample of Fall's work as a whole; as such, it is nearly as personal as an autobiography. . . . That the collection includes an excellent outline of Vietnamese history, a discussion of the basic issues of the war, and an emotive picture of Vietnam, 1967, speaks to the depth of Fall's knowledge and the scope of his concerns.Bernard B. Fall was 40 years old when he was killed by a booby trap in northern South Vietnam on February 21, 1967. By the time of his death he had already authored seven books on Vietnam, most notably Street Without Joy (0-8117-1700-3), an indictment of French intrusion into Indochina and a warning to American forces just beginning their involvement. Last Reflections on a War, first published shortly after Dr. Fall's death, is a tribute to his life's work: It contains the only known autobiographical account of his life, several previously unpublished articles, notes for "Street Without Joy Revisited," and transcripts of Dr. Fall's tape recordings, including his last recorded words.Bernard Fall was born in France and fought with the French Resistance during World War II. Later, as professor of International Relations and accomplished author, he was one of the most influential academic critics of U.S. policy in Vietnam.